Cardiovascular risk factors before and during pregnancy: Does pregnancy unmask or initiate risk? - Harville Emily W; Crook Carrie E; Bazzano Lydia A; Woo Jessica G; Burns Trudy L; Raitakari Olli; Urbina Elaine M; Venn Alison; Jacobs David R; Steinberger Julia; Sinaiko Alain; Dwyer Terence; et al. (Wiley, 2022)
Objectives: To understand if pregnancy unmasks previously silent cardiovascular (CV) adverse factors, or initiates lasting injury.
Methods: Pre-pregnancy and during pregnancy CV risk factors (blood pressure, fasting lipids, and glucose) from 296 women belonging to studies in the International Childhood Cardiovascular Cohort (i3C) Consortium, a group of studies assessing the relationship between child and adolescent CV risk factors and adult outcomes, were used. Correlation coefficients between the pre- and during pregnancy measures were calculated, and the mean difference between the measures was modeled with adjustment for age, body mass index, race, smoking, and study.
Results: Measures were strongly correlated at pre- and during-pregnancy visits (p < 0.01), with r of between 0.30 and 0.55. In most cases, the difference between pre-pregnancy and during-pregnancy did not differ significantly from 0 after adjustment for confounders. Stratification by gestational age indicated stronger correlations with measurements obtained during the first and second trimesters than the third. The correlation did not differ by the time elapsed between the pre-pregnancy and pregnancy visits.
Conclusions: Pre- and during-pregnancy CV risk factors are moderately well correlated. This may indicate that susceptible women enter pregnancy with higher risk rather than pregnancy inducing new vascular or metabolic effects.